Iterative reconstruction of the wave speed for the wave equation with bounded frequency boundary data. (28th January 2016) - Datchev, Kiril; Hoop, Maarten V de
Abstract: We study the inverse boundary value problem for the wave equation using measurements of waves emitted by band-limited boundary sources as the data. We prove how to choose classes of nonsmooth coefficient functions so that optimization formulations of inverse wave problems satisfy the prerequisites for the application of steepest descent and Newton-type iterative methods.